Minat Siswa Terhadap Musik : Studi Kegiatan Ekstrakurikuler di SMP Negeri 8 Padang - Ade Agus Saputra; Tulus Handra Kadir; Syahrel Syahrel (SENDRATASIK UNP, 2013)
Abstract This research was aimed at revealing the students’ interest toward music throught observing their extracurricular activities in music at SMP Negeri 8 Padang. This research used descriptive qualitative method. The result of the research indicated that before the part-time teacher paid, the student had no interest in music, instead they joined some musical activities out of the school. However, after the part-time teacher worked with them and the program was organized, the students started to show their passion on music. Shortly, the students’ interest was likely to rise as the goal and the target of an activity were defined clearly.   Keyword : Interest, music, extracurricular activities, descriptive, qualitative.